Queering Minoritarian In_Visibilities in Art & Visual Culture Renegotiated. Introduction to the Special Issue - Nastold, Friederike (Göttingen, 2026)
Visibility, invisibility, and political agency have developed into a solid triad in the recent past. My long-time accomplice in science and art Thari Jungen and I were thinking a lot about this and the associated ambivalences of visibility (Schaffer 2008) again in summer 2023. The reason for this revisit was the conference Sichtbar machen – werden – sein: in queer_feministischer Perspektive von Kunst und Design (June 2023), taking place at the Muthesius Academy of Fine Arts and Design in Kiel. I would, therefore, like to share some introductory thoughts from our engagement with the affirmation of visibility and, in particular, highlight the ambivalences of visibility that go hand in hand with this. This serves as a basis for the introduction of the present Special Issue entitled “Queering Minoritarian In_Visibilities in Art & Visual Culture Renegotiated” and at the same time as an invitation to interweave the various contributions of it. Firstly, Thari Jungen and I asked ourselves why the paradigm of visibility not only opens up a dichotomy between invisible powerlessness and powerful visibility, but may also reproduce the ambivalences of the dominant, marginalizing logic of representation. Secondly, we asked ourselves what exactly the political nature of visibility is if the production of visibility is to become effective as a political act. And finally, which accomplices require visibility to become political? (Jungen; Nastold 2025).
Keywords: Kultur; 300 Sozialwissenschaften; Design; Sichtbarkeit